Implementation of an early childhood mental health consultation pilot in Virginia: Critical tensions and implications for scale-up - Partee, Ann M.; Sachdeva, Shubhi; Bivona, Marissa A.; Clayback, Kelsey A.; Miller-Marshall, Sasha; Parker, Kyra; Alamos, Pilar; Frank, Cloe; Downer, Jason T.; Williford, Amanda P. (Frontiers in Education, 2023)
Early childhood mental health consultation (ECMHC) is a targeted prevention service that aims to build the capacity of early care and education (ECE) professionals and foster supportive environments that promote children’s social–emotional competence and improve mental health and well-being. A key challenge to delivering ECMHC at scale is navigating complex multi-level factors to maximize successful implementation and program benefits at scale. The current study describes the implementation tensions arising during the first year of a pilot ECMHC program conducted in partnership across multiple agencies and a state’s department of education. In the 2021–2022 pilot year, ECMHC was offered as a free service to ECE programs in one large region of Virginia, with the goal of examining feasibility to scale statewide in future years. Consultation was implemented in 45 preschool classrooms across 30 programs. Implementation data were collected using consultation logs and participant surveys, and 20 participants (educators, families, program directors) participated in focus groups. Three implementation tensions are highlighted in this paper: (1) ideal plans versus reality of a new ECMHC roll-out; (2) how to support ECE professionals’ practice as it relates to children’s behavior, without contributing to a deficit view that children need to be “fixed;” and (3) systemic factors in the early childhood field that undermine the implementation and effectiveness of ECMHC. For each tension, we provide context from the larger literature on ECMHC, describe relevant decision points from Virginia’s pilot ECMHC program, and present implementation data to illustrate these tensions in practice. We conclude with reflections on lessons learned that have implications for other ECMHC and SEL intervention scale-up efforts.